Validity of cytology in the diagnosis of small cell lung carcinoma - Krivokuća Živko; Tatomirović Željka; Cvetković Gordana; Džambas Jelena; Škuletić Vesna; Ristić Saša (Vojnosanitetski Pregled)
Background/Aim. Small cell lung carcinoma (SCLC) is the most aggressive form of lung cancer. Patients with SCLC generally appear in a locally advanced or disseminated stage, when small biopsies and/or cytological materials are the only possibility for diagnosis. The aim of this study was to evaluate the validity of cytology in the initial diagnosis of SCLC, comparing cytological with histological findings of small biopsies. Methods. The retrospective study included 200 patients with cytological diagnosis of SCLC, established in the period from 2016 to 2018 based on examination of the exfoliative material (sputum), as well as abrasive and aspiration materials obtained during bronchoscopy. In the same act, bronchoscopic materials were taken for cytological and histological diagnosis. Cytological materials were stained by May Grünwald Giemsa and histological ones using hematoxylin-eosin and immunohistochemical stains. Results. The most frequently sampled materials were: transbronchial needle aspiration (TBNA) in 72.2% of the patients and bronchial brushing in 18.54% of the patients, in the following order: bronchial aspirate in 4.88%, tru-cut needle biopsy in 5.37%, and sputum in 2.44% of the patients. In 91.5% (183/200) of the patients cytological diagnosis of SCLC was histopathologically confirmed. Among 17 patients whose cytological diagnosis of SCLC was not confirmed histopathologically, another type of tumor was histopathologically proved for 12 (6%) of them: in 6 cases non SCLC not otherwise specified, and in each per one squamocellular carcinoma, adenocarcinoma, large cell carcinoma, mixed tumor (NSCLC with a neuroendocrine component), lymphoma and sarcoma. Finally, in five patients histological material was false-negative. Conclusion. Cytological diagnosis of SCLC is a reliable method which yields satisfactory accuracy. The best way is to be interpreted in conjunction with histology of small biopsies. When only cytological materials are available, in doubtful cases, other small round cell tumors, and poorly differentiated NSCLC, must be considered in the differential diagnosis.